Interacting Effect of Catechol-O-Methyltransferase (COMT) and Monoamine Oxidase A (MAOA) Gene Polymorphisms, and Stressful Life Events on Aggressive Behavior in Chinese Male Adolescents - Wang, Meiping; Li, Hailei; Deater-Deckard, Kirby; Zhang, Wenxin (Frontiers in Psychology, 2018)
Numerous studies have demonstrated that both Catechol-O-methyltransferase (COMT) gene and monoamine oxidase A (MAOA) gene have been involved in aggressive behavior, as have stressful life events. However, most of available evidence was based upon single gene or single gene-environment design, which is limited in accounting for the variance of aggressive behavior, a complex phenotype. This study examined the possible gene × gene × environment interactions between stressful life events (SLE, interpersonal problems and academic pressure) and two genetic polymorphisms (MAOA T941G and COMT Ala22/72Ser) correlated with aggressive behaviors in a sample of 658 Chinese male adolescents. Mothers and teachers reported on adolescents’ aggressive behavior using Achenbach’s Child Behavior Checklist and Teacher Report Form, respectively. Adolescents completed Self-Rating Life Events Checklist. Saliva samples were collected for DNA analysis. The results revealed no main effects of MAOA T941G and COMT Ala22/72Ser polymorphisms on male adolescents’ aggressive behaviors. However, a two-way interactive effect of interpersonal problems and MAOA T941G genotype on teacher-reported aggressive behavior was observed: Adolescents with lower activity of MAOA T allele, but not those with MAOA G allele, exhibited greater aggressive behavior with an increase in interpersonal problems. A three-way interaction among COMT Ala22/72Ser and MAOA T941G polymorphisms, and SLE in the academic pressure on aggressive behavior was also identified. Among adolescents with lower activity of COMT GT/TT genotype and MAOA T allele, the higher level of academic pressure was significantly linked with an amplification of aggressive behavior, whereas this association didn’t exist among those with other genotypes. The present study presents the first evidence of COMT × MAOA × SLE interaction effect on male adolescents’ aggressive behavior, highlights the importance of considering distinct domains of stressful events and information bias when examining the effect of MAOA and COMT on aggressive behavior, and thereby contributes to MAOA gene-aggression and COMT gene-aggression literature. Keywords: MAOA, COMT, stressful life events, aggressive behavior, gene  gene  environment interaction